HUBUNGAN PEMAHAMAN ORANG TUA TENTANG PERKEMBANGAN EMOSIONAL ANAK DENGAN KEKERASAN VERBAL PADA ANAK USIA 3-4 TAHUN DI DESA SEJATI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Fuja Desmara; Enda Puspitasari; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research is motivated by the low understanding of parents about the emotional development that exists in children in the Sejati village Rambah Hilir district Rokan Hulu regency relating to verbal abuse perpetrated by parents, where parents still use verbal abuse in advising children, and parents still have the mindset that what parents do to their children is all true. The research aims to determine the relationship of parents understanding of children emotional development with verbal abuse in children aged 3-4 years in the Sejati village. This type of research is quantitative using a correlation research approach. As for the population of this research are parents who have children aged 3-4 years in the Sejati village amounting to 70 parents, the sample of this research is 70 parents taken using saturated sampling. Data collection techniques used were test and questionnaires. Data analysis techniques used the Pearson Product Moment correlation using the program SPSS version 24. Based on the results of hypothesis testing obtained there is a negative and significant relationship between parents understanding of children emotional development with verbal abuse in children aged 3-4 years in the Sejati village. This can be seen from the correlation coefficient of rxy=-0,448, and the significance level of 0,000<0,05. The level of relationship between parents understanding of the emotional development of children with verbal abuse in children aged 3-4 years in the Sejati village included in the medium category with the coefficient of determination produced 20,1% which means that parents understanding of children emotional development gives an effect of 20,1% on verbal abuse in children.Key Words: Parents Understanding Of The Emotional Development Of Child, Verbal Abuse